Konstruksi Dan Teknik Pegoperasian Pancing Tongkol di Perairan Kepulauan Seribu - Zhulmaydin Chairil Fachrussyah; Roy Bakary; Jufriyanto Umar; Dadang Alim (Universitas Gorontalo, 2019)
Abstract. Tongkol Hook are not found in any fish catching classification, so the information on these fishing gear is rarely outstanding. Based on this, this research is important to be done to provide additional information about tongkol hook in Thousand Islands especially concerning construction and operation technique. This research was conducted in July-August 2017. Data collection was done in several places, namely the waters around Panggang Island, Pramuka Island, Pulau Tidung and Pulau Semak Daun. The analysis was conducted using a comparative descriptive method of design and construction of fishing gear. In this analysis shows and describes the size, constituent material, and the sum of each portion of the fishing equipment of the tongkol hook. The results of the research found that the construction of tuna fishing line consists of: Main Line, Branch Line, Panggal Point, Fishing Eye, Artificial Feed, Buoy, Nets, and Swivel. Techniques The operation of this fishing gear is done by circling the swarms of fish and then the fishing line is released in the herd of fish.